Indigenous and minor leafy vegetables - Pragya, Pragya; Gangopadhyay, K K; Ranjan, J K; Singh, B K (Indian Horticulture, 2020)
India is home to a large number of leafy vegetables which are blessed with enormous potential but practically very few information is available on their production and quality attributes. Consumption of these vegetables is mostly confined to the people living in the areas where they grow with little or no production on commercial scale. Though in the recent years few of them got attention by the growers and consumers worldwide, still most of them are in neglected state and need focused attention for achieving nutritional and health security.